Burden of Dengue Infection and Disease in a Pediatric Cohort in Urban Sri Lanka - Tissera, Hasitha (The American Society of Tropical Medicine and Hygiene, 2014)
Dengue is the most significant arthropod-borne viral infection of humans. Persons infected with dengue viruses (DENV) have subclinical or clinically apparent infections ranging from undifferentiated fever to dengue hemorrhagic fever/shock syndrome. Although recent studies estimated that the Indian subcontinent has the greatest burden of DENV infection and disease worldwide, we do not have reliable, population-based estimates of the incidence of infection and disease in this region. The goal of this study was to follow-up a cohort of 800 children living in a heavily urbanized area of Colombo, Sri Lanka to obtain accurate estimates of the incidence of DENV infection and disease. Annual blood samples were obtained from all children to estimate dengue seroprevalence at enrollment and to identify children exposed to new DENV infections during the study year. Blood was also obtained from any child in whom fever developed over the course of the study year to identify clinically apparent DENV infections. At enrollment, dengue seroprevalence was 53.07%, which indicated high transmission in this population. Over the study year, the incidence of DENV infection and disease were 8.39 (95% confidence interval = 6.56–10.53) and 3.38 (95% confidence interval = 2.24–4.88), respectively, per 100 children per year. The ratio of clinically inapparent to apparent infections was 1.48. These results will be useful for obtaining more accurate estimates of the burden of dengue in the region and for making decisions about testing and introduction of vaccines.